All fibre laser source and specialty fibre for 2μm laser applications - Tse, Chun Ho (2015)
In military operations, soldiers often have to go through various challenging terrains. Thus, devices used in military applications have to be compact, lightweight and rugged. For example, the light detection and ranging (LIDAR) system which transmits light to precisely profile atmospheric cloud, aerosol scattering and air flow, is crucial for the weather forecasting, environmental monitoring and aircraft safety. With the development of high-speed data processing technique, the LIDAR performance and usage are ultimately constrained by the availability of an eye safe, compact laser source with widely tunable range. Different from the bulky free-space optics based laser source, our project aims to achieve an all fibre based laser source that is low cost, light and compact, alignment hassle free. Thulium (Tm) doped fibre lasers have gained much interest in recent years because of its possible applications in the medical, defense, ranging and atmospheric sensing areas. However, most of these applications have very specific requirement for the wavelength of the laser source used. Thus, it is critical for the laser source to be wavelength-tunable, to correctly match each of the specific operating wavelengths. In our project, theoretical modeling of Tm-doped fibre laser was done based on the general rate equations for the energy levels of Tm3+. Based on this theoretical modeling, we demonstrate experimentally a broadly wavelength-tunable, CW Tm-doped all fibre ring laser. The wavelength tunability in the fibre laser is enabled in the laser cavity using a fibre Sagnac loop filter constructed with a length of high birefringence (HiBi) fibre, a polarization controller and a 3 dB coupler. Tuning of the lasing wavelength can be realized by careful adjustment of the two polarization controllers in the fibre ring laser. We experimentally demonstrate a setup that can be tuned for 48nm from 1924.2 nm to 1972.2 nm. In addition, we also study on the effect and optimization of the HiBi fibre length with overall wavelength tuning range. Laser sources in the 2μm region and above also have great potential for industry applications such as spectroscopy, sensing, industry processing, medical diagnosis, surgery and various defence related applications. However, transmission and delivery of laser signal above the 2μm region in convention silica based fibres is limited. Heavy metal oxide glasses exhibiting high transmission and high nonlinearity in the Mid-Infra-Red spectrum but are often difficult to manufacture in large sizes with optimized physical and optical properties. Lead-bismuth-gallium fibres have shown attractive properties such as high thermal stability, lower transmission losses, and broad transmission window. It is also suitable for achieving high nonlinearities for various applications. In this thesis, the author shows the design and fabrication of lead-bismuth-gallium optical fibres capable of transmission of light signal from 2μm with the potential of extending even further into the mid infra-red spectrum.